ANALISIS KINERJA RANTAI PASOK MENGGUNAKAN METODE SUPPLY CHAIN OPERATIONS REFERENCE (SCOR 12.0) (STUDI KASUS PT.XYZ) - Muhammad Fauzie Mertosono, (2022)
PT. XYZ is a pharmaceutical company that makes medicines, distributes medical devices, and offers food. It is one of the earliest companies in the pharmaceutical service chain. Because these organizations never measure overall performance, they often encounter problems in the planning, procurement, manufacturing, and delivery stages. Therefore, performance evaluation is needed to determine supply chain performance using the Supply Chain Operation Reference (SCOR12.0) approach. Measurements are carried out in stages, including identification of the SCOR 12.0 matrix and validation of Key Performance Indicators (KPI). Based on research findings, the average supply chain flow performance value achieved is 60.6. However, there are still several performance indicators that are a priority for improvement, namely those where the indicators are RS.3.28 with a score of 37.5, RS.3.10 with a score of 28.8, RL.3.35 of 41.67, RL.3.32 with a score of 41 .67, RL.3.32 of 40, and CO.3.16 with a score of 42.94. By making improvements to these indicators, it is expected to help improve supply chain performance at the company